2010
DOI: 10.1038/nchembio.423
|View full text |Cite
|
Sign up to set email alerts
|

A small-molecule inhibitor shows that pirin regulates migration of melanoma cells

Abstract: The discovery of small molecules that bind to a specific target and disrupt the function of proteins is an important step in chemical biology, especially for poorly characterized proteins. Human pirin is a nuclear protein of unknown function that is widely expressed in punctate subnuclear structures in human tissues. Here, we report the discovery of a small molecule that binds to pirin. We determined how the small molecule bound to pirin by solving the cocrystal structure. Either knockdown of pirin or treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 48 publications
2
110
1
Order By: Relevance
“…The single human PRN has been shown to interact with the nuclear factor I/CCAAT box transcription factor (Wendler et al ., 1997) and the oncoprotein Bcl-3 (Dechend et al ., 1999). It has been implicated in several processes, including transcriptional control, apoptosis, migration and cellular senescence of melanoma cells (Courtois and Gilmore, 2006; Ahmed and Milner, 2009; Miyazaki et al ., 2010; Licciulli et al ., 2011). Plants normally have small complements of PRN genes, most of which have poorly understood roles.…”
Section: Introductionmentioning
confidence: 99%
“…The single human PRN has been shown to interact with the nuclear factor I/CCAAT box transcription factor (Wendler et al ., 1997) and the oncoprotein Bcl-3 (Dechend et al ., 1999). It has been implicated in several processes, including transcriptional control, apoptosis, migration and cellular senescence of melanoma cells (Courtois and Gilmore, 2006; Ahmed and Milner, 2009; Miyazaki et al ., 2010; Licciulli et al ., 2011). Plants normally have small complements of PRN genes, most of which have poorly understood roles.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report shows that PIR controls melanoma cell migration through the transcriptional regulation of snail homolog 2, SNAI2 (previously SLUG). 16 Other reports described quercetinase enzymatic activity, 17 and regulation of apoptosis 18,19 and stress response, unveiling a high degree of cell-type and species specificity in PIR function.…”
mentioning
confidence: 99%
“…Pirin has additionally been linked to the metastasis of melanoma cells (22,23). It has been shown that pirin expression is significantly up-regulated in the spleen and kidney of cytosolic superoxide dismutase (SOD)-deficient mice (24).…”
mentioning
confidence: 99%